Adapting to new normal learning, how ready are the aspiring teachers? - Dedi Irwan (IKIP PGRI Pontianak, 2022)
This study aimed to describe readiness in online learning and aspects that support online learning experienced by students of the English Education Study Program of IKIP PGRI Pontianak. This study used descriptive statistical method. The data collection technique is an indirect communication technique (questionnaire). A close-ended questionnaire readiness in online learning by (Dray et al., 2011) was distributed to 563 students from semester one to semester seven of the IKIP PGRI Pontianak English Education Study Program. This study found that pre-service teachers were ready for the online learning process on campus. The results showed that the average score was 40% from points 1, 4 and 5 about mental access, the results showed that students were not only mentally prepared but also able to add digital experiences about technology. An average score of 94.5% from points 2 and 6 about access to materials, the results of the study show that students are not only material ready but also have network connections in online learning. While the average score of 99.3% is the readiness of pre-service teachers in accessing use and is also very supportive. Not only that, pre-service teachers are supported in 4 aspects such as mental access, material access, skill access and usability access. Based on the research results, pre-service teachers should not only be oriented to conventional teaching, but focus more on the learning process in utilizing technology.